Desain Media Pembelajaran Berbasis Hypnoteaching untuk Meningkatkan Pemahaman Materi Bumi di Kelas V SD - Warto, Warto; Buchori, Achmad; Ngatmini, Ngatmini (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
Addressing fifth-grade students’ challenges in comprehending abstract geological concepts such as Earth’s layers, water cycles, and tectonic plate movements, this study focuses on designing hypnoteaching-integrated learning media for the “Let’s Get to Know Our Earth” material. Utilizing the Research and Development (RD) method with the ADDIE model, the analysis and design stages were prioritized. Needs assessments via classroom observations, teacher interviews, and literature reviews revealed gaps in students’ conceptual grasp of dynamic Earth processes. The developed media a twenty minute educational video combines animated visualizations, suggestive narratives, and interactive pedagogical components tailored to elementary learners. Structured into introduction, core content delivery, group activities, quizzes, and motivational closure, the resource aligns with cognitive and engagement needs of young students. Preliminary teacher validations underscore its effectiveness in capturing attention, fostering motivation, and clarifying complex scientific phenomena. This innovation presents a potential alternative for enhancing IPAS (Natural and Social Sciences) instruction, promoting interactive learning experiences. Further studies are encouraged to empirically test the media’s efficacy in classroom applications and investigate its adaptability to diverse subject matters.